Co-solvent exfoliation of layered titanium diboride into few-layer-thick nanosheets. Issue 18 (15th December 2020) - Patidar, Rishabh; Gunda, Harini; Varma, Akash K.; Gawas, Ramchandra; Das, Saroj Kumar; Jasuja, Kabeer
Abstract: In this work, we present an approach to nanoscale titanium diboride (TiB2 ), a layered ceramic from the metal diboride family, by investigating its interaction with a co-solvent containing water and isopropanol (IPA). It is gradually being established that layered metal diborides can be exfoliated in liquid phase to yield 2D counterparts. However, these reports have not yet systematically investigated the suitability of a solvent to exfoliate these ionic layered materials. Such a prospect is primarily limited by the fact that the theories available to rationally select exfoliating solvents are applicable only for van der Waals (vdW) layered materials. We show that it is possible to identify an optimal exfoliating medium for TiB2 by using co-solvents. We tested the exfoliation of TiB2 in isopropanol (IPA)-water co-solvent mixtures at different IPA concentrations, and established that a 10% isopropanol-water co-solvent results in optimal exfoliation. The resultant nanosheets are extremely thin ( 3–5 nm) and exhibit a mild degree of oxy-functionalization. We observed that the original structural integrity of nanosheets (TiB2 lattice) is maintained to a large extent after exfoliation. We also validated the findings by using Surface Tension Component Matching (STCM) and studied the exfoliation of TiB2 in acetonitrile (ACN). This resulted in a lower degree of exfoliation as expected, but led us to obtain nearly pristine TiB2 nanosheets. The new physical insights presented in this work can serve as a guide to predict the exfoliation of TiB2 in other prospective solvents.